The Impact of Debt Maturity on Stock Price Crash Risk with an Emphasis on Information Asymmetry - Vahid Taghizadeh Khanqah (Journal of Asset Management and Financing, 2018)
Short-term debt subjects managers to frequent monitoring, thus effectively reducing managerial discretion and enhancing information disclosure. Since lenders are more sensitive to decreases than increases in firm stock price, they have strong incentives to scrutinize borrowers and gather information about their financial conditions and future prospects. This research aims to study the economic concequences of debt maturity, to the impact of debt maturity choice on stock price crash risk of listed companies in Tehran Stock Exchange. In this regard, 120 companies were evaluated for the period 2008-2013. To test the hypothesis of the study panel data is used by software Eviews 7. We find that firms with a larger proportion of short-term debt tend to have lower future stock price crash risk, consistent with short-term debt playing an effective monitoring role over managers and constraining their bad news hoarding behavior. Our results also show that the inverse relation between short-term debt and future crash risk is more pronounced among firms with higher degree of information asymmetry. Overall, our paper shows that short-term debt not only preserves creditors’ interests, but also protects the value of shareholders.